Robustness assessment of RC frame buildings with HPFRCC subjected to progressive collapse - Hamid Mirzahosseini; S. Mohammad Mirhosseini; Ehsanollah Zeighami (Results in Engineering, 2023)
Beam-column joints are one of the most critical components of RC structures, affecting the structure's performance under different types of loads. In recent years, some researchers have considered high-performance fiber-reinforced cementitious composites (HPFRCCs) as an alternative to conventional concrete for improving the performance of beam-column joints. The effects of HPFRCC materials on the robustness of reinforced concrete structures subjected to progressive collapse were investigated in this study. To this end, the method proposed by Fascetti et al. was utilized to assess the robustness of three five-story RC buildings with a moment-resisting frame system. The buildings were designed as special moment frames (SMF), intermediate moment frames (IMF), and intermediate moment frames with HPFRCC at joints (IMF-H) per ACI 318–14. The OpenSees finite element platform has been widely used for 3D buildings simulation and nonlinear analysis. In this study, the analyses and calculated robustness indices indicated that using HPFRCCs materials in beam-column joints significantly improved the robustness of concrete moment frames subject to progressive collapse. Furthermore, the damage distribution based on plastic rotation results confirmed that the robustness of concrete moment frames with HPFRCC joints subjected to progressive collapse was significantly improved.